Corporate law and corporate governance. The Hungarian experience - Istvan Czajlik; Janos Vincze (Hungarian Academy of Sciences, Institute of Economics, 2004)
In this paper our aim was to establish legal facts for Hungary in detail, to put the countrys situation into international context, and to find new avenues for comparative research. We updated investor protection indicators already existing in the literature, while determined enforcement indicators for the first time. We hypothesize that besides indicators the dynamics of legislation must be an important topic for research. An analysis of the dynamics of legislation in Hungary indicates that two tendencies could be observed. one responding to actual challenges, leading to more reliance on the interpretation of law by judges, the second following the German-tradition resulting in more bright line rules, and more complicated legal regulation. To make the former workable political and financial independence is a necessary, though not sufficient, condition. We emphasize that though investor protection supports the supply of outside funds, there is a demand side to external finance, and more prudential regulation can lead to less demand for external finance.
Keywords: 330